SheSave: desarrollo e implementación de una aplicación móvil para la notificación de emergencias que optimice el tiempo de respuesta a la atención de las mujeres (2024)
This project addresses the problem of insecurity in public spaces in Bogota from a gender perspective, recognizing the specific vulnerability of women to events of risk and fear. It is clear that in the urban environment a violent and hostile environment for women is perceived, in response to this, the development corresponding to the prototype of the mobile application called SheSave is implemented, which offers an effective alert system to notify trusted contacts and mitigate or avoid dangerous situations.